Analysis of Critical Thinking Skills on the Project of Strengthening the Pancasila Profile of Grade IV Students of Plumbon Elementary School (Universitas Pendidikan Indonesia (UPI), 2024)
The purpose of this study was to analyze the critical thinking skills of grade 04 Plumbon 03 Public Elementary Schools in the project to strengthen the profile of the Pancasila Merdeka Curriculum and the results of this study are expected to be used as a reference source for research in the field of critical thinking skills of elementary school students. The research method uses a qualitative descriptive research method. data collection techniques use observation, interviews, and documentation while data analysis techniques use the Miles and Huberman model, namely through several processes of data collection, reduction, and presentation. Research time from May to June 2023, location in Bulu Hamlet, Plumbon, Mojolaban, Sukoharjo. This study used observation, interview, and documentation methods involving all 9 grade IV students and 1 class teacher. The results of the study can be concluded that the critical thinking skills of fourth-grade students at SD Negeri Plumbon 03 in the Pancasila Student Profile Strengthening Project (P5) are high because they have mastered the five indicators of critical thinking skills, namely observation, analysis, evaluation, inference, and explanation. This can happen because it is supported by factors of critical thinking skills, namely basic cognitive abilities, experience, interpersonal skills, educational and social environment, and the ability to manage emotions.